1995
DOI: 10.1177/43.7.7541817
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring morphology and signal during non-radioactive in situ hybridization procedures by reflection-contrast microscopy and transmission electron microscopy.

Abstract: We analyzed the effects of steps in RNA in situ hybridization (ISH) procedures on morphology and hybridization signal with reflection-contrast microscopy (RCM) and transmission electron microscopy (TEM). In chessboard experiments, a range of fixatives containing formaldehyde, glutaraldehyde, or both, and various permeabilization protocols, including ethanol and pepsin treatment, were investigated. A transfected rat fibroblast cell line that harbors an inducible human cytomegalovirus immediate early (IE) transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…These groups have used animal sera to block nonspecific binding of antibodies to tissue specimens; in contrast, by using bovine serum albumin instead of sera, Hermanson et al (1994) have been able to perform immunohistochemistry prior to ISH with no appreciable loss of signal or unacceptable background staining. The need to permeabilize sections with proteolytic pretreatment for ISH may result in a loss of the epitope of interest for immunohistochemistry (Macville et al 1995). Consequently, execution of immunohistochemistry prior to ISH seems attractive to us.…”
Section: Discussionmentioning
confidence: 99%
“…These groups have used animal sera to block nonspecific binding of antibodies to tissue specimens; in contrast, by using bovine serum albumin instead of sera, Hermanson et al (1994) have been able to perform immunohistochemistry prior to ISH with no appreciable loss of signal or unacceptable background staining. The need to permeabilize sections with proteolytic pretreatment for ISH may result in a loss of the epitope of interest for immunohistochemistry (Macville et al 1995). Consequently, execution of immunohistochemistry prior to ISH seems attractive to us.…”
Section: Discussionmentioning
confidence: 99%
“…0nly slightly adjusted (EM) methods are needed for producing RCM-(EM) specimens. Macville et al (1995) also studied RCM in combination with (EM). They reported that (EM) morphology could be predicted and extrapolated to a large extent from the RCM images.…”
Section: Combination Of Rcm and Electron Microscopy (Clem)mentioning
confidence: 99%
“…Especially in cases where difficulties arise with recording of faint staining of, for example, small nucleic acid target sequences, RCM detection is preferable over brightfield detection. Initial ISH studies used the reflection properties of the HRP-DAB reaction product and resulted in the efficient visualization of DNA targets, ranging from repetitive to single-copy sequences (10-40 kb), and mRNA sequences (Landegent et al 1985;Ambros et al 1986;Cornelese-Ten Velde et al 1988;Multhaupt et al 1989;MacVille et al 1995). The application of other enzyme precipitation reactions for RCM detection, however, was hampered by the fact that most reaction products are only stable in aqueous-based mounting media (see Table 5) and, thus, are unstable in immersion oil, which is required in this procedure.…”
Section: Probe Visualization By Reflection Contrast Microscopymentioning
confidence: 99%